The nexus of climate change, urban infrastructure and sustainable development in developing countries. Issue 1 (March 2021) - Oloke, O.C.; Fayomi, O.S.I.; Oluwatayo, A.; Adagunodo, T.A.; Akinwumi, I.I.; Amusan, L.M.
Abstract: This study weighed in on the topical issue of climate change impacts and sustainable urban development in developing countries. Climate change is a global challenge that is much discussed at national and international fora. The study reflects on the lot and plight of cities and peri-urban communities in developing countries in the face of lopsided attention on climate change. Extant studies, articles, local and international reports on climate change, urbanization and infrastructure, extant literatures were reviewed to establish the perspective and position of the study. The study examined the global threats of climate change and the local impact of disasters to urban dwellers in developing countries like Nigeria. It further shed light on urbanization process and the state of infrastructure in developing countries. Vulnerability of cities in the areas of infrastructure was brought to the fore with a view to improving the capacity and preparedness against climate change impact. Concepts of climate change, urbanization challenge, urban infrastructure, sustainable development were reviewed to contextualize the study. The study concluded by advocating for positive urbanization to mitigate the effect of climate change and foster sustainable development agenda in developing countries.